Crystallization behavior and polymorphism of poly(1, 4‐butylene adipate): Effect of anhydrous orotic acid as nucleating agent. Issue 5 (12th October 2015) - Yang, Jinjun; Chen, Yichun; Hua, Lei; Liang, Rong; Zhu, Dianxing
ABSTRACT: The effect of anhydrous orotic acid (OA), as a biocompatible nucleating agent (NA), on the non‐isothermal and isothermal crystallization behaviors, polymorphic crystalline structure and phase transition of poly(1, 4‐butylene adipate) (PBA) was investigated. It is found that the OA increased the crystallization temperature of the PBA in the non‐isothermal crystallization process and decreased the crystallization time of the PBA in the isothermal crystallization process. Meanwhile, the spherulite size decreased and spherulite density increased for the PBA. The OA favored the formation of the PBA α‐form crystal, compared to the neat PBA. In addition, upon incorporation of the OA, the β ‐ to ‐ α phase transition rate was enhanced significantly. Mechanisms for the preferential formation of the PBA α‐form crystal and the accelerated phase transition have also been proposed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42957. Abstract :